Propiedades físicas del agar de Gracilariopsis tenuifrons (Gracilariaceae) en Sucre, Venezuela - Zecchinel F., E. (2000)
The yield, gel strength, gelling and melting temperatures of Gracilariopsis tenuifrons agar from Guayacán, Araya Peninsula, Sucre State, Venezuela were determined. Yield values with and without alkali treatment ranged from 23.22 to 39.57% and from 16.29 to 22.42% respectively, while gel strength with alkali treatment fluctuated betwen 699.31and 1231.69 g/cm2 and without treatment varied from 278.0 to 691.06 g/cm2. Gelling and melting temperatures were in the range reported for other agarophytes. Considering gel strength, the agar quality of G. tenuifrons was higher than in other species and its exploitation in economically feasible.